Anything but a Walk in the Park: Framing Analysis of the Adirondack State Park Land Classification Conflict - Sandrow, Cheryl A.; Feldpausch-Parker, Andrea M.; Vidon, Elizabeth S.; Parker, Israel D. (Frontiers in Communication, 2018)
State and national park land management is rife with conflict, be it either over how land is managed within the park or how it affects adjacent private lands. The Adirondack Park in upstate New York is an especially interesting case due to its unique mix of public and private lands within the boundaries of the park, often referred to as the Blue Line. A recent land acquisition by the New York State Department of Environmental Conservation (NYSDEC) and the resultant land classification process is the most recent conflict in the region in a long line of land use/land designation conflicts. In the wake of recent attempts for greater collaboration, we explored this conflict by conducting a framing analysis of both stakeholders’ online presence (i.e., websites and blogs) and local news media coverage of the classification process. Primary stakeholders included local town residents, sportsmen groups, NYSDEC, Adirondack Park Agency, local government, and environmental groups. We found that stakeholder groups’ online materials utilized frames to describe their objectives based on different values. Dominant frames included a “reasonable access” frame used by residents and town officials to highlight rights to accessible use. Environmental groups heavily used an “environmental protection” frame, highlighting the ecologically important wetlands and opportunity to increase lands designated as “Wilderness”. In news media articles, the dominant frame was the “conflict frame”, portraying the decision-making process as riddled with tension and incompatibility. These frames indicate that the conflict over land classification stems from different values of accessibility and strong wilderness protection as well as being communicated as intractable by the media.